The bacterial microbiota of Hunner lesion interstitial cystitis/bladder pain syndrome. (5th July 2021) - Nickel, J. Curtis; Ehrlich, Garth D.; Krol, Jaroslaw E.; Ahmed, Azad; Sen, Bhaswati; Bhat, Archana; Mell, Joshua C.; Doiron, R. Christopher; Kelly, Kerri‐Lynn; Earl, Joshua P.
Abstract : Objective: To undertake the first comprehensive evaluation of the urinary microbiota associated with Hunner lesion (HL) interstitial cystitis/bladder pain syndrome (IC/BPS). Despite no previous identification of a distinct IC/BPS microbial urotype, HL IC/BPS, an inflammatory subtype of IC/BPS, was hypothesized most likely to be associated with a specific bacterial species or microbial pattern. Participants and Methods: The bacterial microbiota of midstream urine specimens from HL IC/BPS and age‐ and gender‐matched IC/BPS patients without HL (non‐HL IC/BPS) were examined using the pan‐bacterial domain clinical‐level molecular diagnostic Pacific Biosciences full‐length 16S gene sequencing protocol, informatics pipeline and database. We characterized the differential presence, abundances, and diversity of species, as well as gender‐specific differences between and among HL and non‐HL IC/BPS patients. Results: A total of 59 patients with IC/BPS were enrolled (29 HL, 30 non‐HL; 43 women, 16 men) from a single centre and the microbiota in midstream urine specimens was available for comparison. The species abundance differentiation between the HL and non‐HL groups (12 species) was not significantly different after Bonferroni adjustments for multiple comparisons. Similarly, the nine differentiating species noted between female HL and non‐HL patients were not significantly different after similar statistical correction. However, four species abundances (out of the 10 species differences identified prior to correction) remained significantly different between male HL and non‐HL subjects: Negativicoccus succinivorans, Porphyromonas somerae, Mobiluncus curtisii and Corynebacterium renale . Shannon diversity metrics showed significantly higher diversity among HL male patients than HL female patients ( P  = 0.045), but no significant diversity differences between HL and non‐HL patients overall. Conclusions: We were not able to identify a unique pathogenic urinary microbiota that differentiates all HL from all non‐HL IC/BPS. It is likely that the male‐specific differences resulted from colonization/contamination remote from the bladder. We were not able to show that bacteria play an important role in patients with HL IC/BPS.